Pregunta
upstudy study bank question image url

\( \left. \begin{array} { l } { \vee 450 . ( 3 x + 1 ) ( 6 - 4 x ) = 0 } \\ { \vee 451 . ( 5 x - 4 ) ( x + 8 ) = 0 } \\ { \vee 452 . ( 6 x + 3 ) ( 9 - x ) = 0 } \end{array} \right. \)

Ask by Welch Chavez. in Russia
Feb 25,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

Решения уравнений: - \( x = -\frac{1}{3}, \frac{3}{2}, \frac{4}{5}, -8, -\frac{1}{2}, 9 \)

Solución

Давайте решим систему уравнений, представленную в виде произведений, равных нулю. Это означает, что хотя бы один из множителей в каждом уравнении равен нулю. Мы будем решать каждое уравнение по отдельности. 1. **Первое уравнение:** \[ (3x + 1)(6 - 4x) = 0 \] Это уравнение равно нулю, если: - \(3x + 1 = 0\) - \(6 - 4x = 0\) Решим каждое из этих уравнений: - Для \(3x + 1 = 0\): \[ 3x = -1 \implies x = -\frac{1}{3} \] - Для \(6 - 4x = 0\): \[ 4x = 6 \implies x = \frac{3}{2} \] Таким образом, решения первого уравнения: \(x = -\frac{1}{3}, \frac{3}{2}\). 2. **Второе уравнение:** \[ (5x - 4)(x + 8) = 0 \] Это уравнение равно нулю, если: - \(5x - 4 = 0\) - \(x + 8 = 0\) Решим каждое из этих уравнений: - Для \(5x - 4 = 0\): \[ 5x = 4 \implies x = \frac{4}{5} \] - Для \(x + 8 = 0\): \[ x = -8 \] Таким образом, решения второго уравнения: \(x = \frac{4}{5}, -8\). 3. **Третье уравнение:** \[ (6x + 3)(9 - x) = 0 \] Это уравнение равно нулю, если: - \(6x + 3 = 0\) - \(9 - x = 0\) Решим каждое из этих уравнений: - Для \(6x + 3 = 0\): \[ 6x = -3 \implies x = -\frac{1}{2} \] - Для \(9 - x = 0\): \[ x = 9 \] Таким образом, решения третьего уравнения: \(x = -\frac{1}{2}, 9\). Теперь соберем все решения вместе: - Из первого уравнения: \(x = -\frac{1}{3}, \frac{3}{2}\) - Из второго уравнения: \(x = \frac{4}{5}, -8\) - Из третьего уравнения: \(x = -\frac{1}{2}, 9\) Итак, все решения системы уравнений: \[ x = -\frac{1}{3}, \frac{3}{2}, \frac{4}{5}, -8, -\frac{1}{2}, 9 \]

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Beyond the Answer

To solve the equations, we can use the Zero Product Property, which states that if a product of factors equals zero, at least one of the factors must be zero. For \( 450. ( 3x + 1)(6 - 4x) = 0 \): Setting each factor to zero gives: 1. \( 3x + 1 = 0 \) ⟹ \( x = -\frac{1}{3} \) 2. \( 6 - 4x = 0 \) ⟹ \( x = \frac{3}{2} \) For \( 451. (5x - 4)(x + 8) = 0 \): 1. \( 5x - 4 = 0 \) ⟹ \( x = \frac{4}{5} \) 2. \( x + 8 = 0 \) ⟹ \( x = -8 \) For \( 452. (6x + 3)(9 - x) = 0 \): 1. \( 6x + 3 = 0 \) ⟹ \( x = -\frac{1}{2} \) 2. \( 9 - x = 0 \) ⟹ \( x = 9 \) To summarize: 1. From \( 450 \): \( x = -\frac{1}{3}, \frac{3}{2} \) 2. From \( 451 \): \( x = \frac{4}{5}, -8 \) 3. From \( 452 \): \( x = -\frac{1}{2}, 9 \) Get ready to unlock those numbers! Math isn't just a crunching of numbers; it's a journey, just like the great stories of problem solvers throughout history! Imagine mathematicians of the past, like Archimedes, who laid the groundwork for modern algebra while pondering the mysteries of the universe and solving practical problems of their time. Even today, these equations have practical uses in fields like engineering, finance, and physics. For instance, you can model everything from the height of a projectile to analyzing profit margins with such equations. Next time you encounter similar quadratic equations, remember that you're not just solving for \( x \), you're solving for various real-world applications, making your understanding incredibly valuable!

preguntas relacionadas

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Álgebra Mexico Feb 26, 2025
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad